Technologie cyfrowe w procesie podejmowania decyzji politycznych w Polsce - Pikul, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article examines the spectrum of digital technologies and digital transformation, in the context of broad political decision-making. Digital technologies are often used interchangeably with terms such as digitization, information technologies, or internet technologies. However, they are present in almost every sphere of life. Political decision-making as a highly complex embedded process that takes place at both the individual and collective level is key to the functioning of the state and results from the sum of individual choices, especially in democratic systems. These processes, influenced by economic, international, and security factors, increasingly rely on digital tools.
Keywords: cyfryzacja; proces decyzyjny; administracja publiczna; partycypacja; bezpieczeństwo cyfrowe; digitization; decision-making; public administration; participations; digital security